Rotavirus Infection Reduces Sucrase-Isomaltase Expression in Human Intestinal Epithelial Cells by Perturbing Protein Targeting and Organization of Microvillar Cytoskeleton - Jourdan, Nathalie (American Society for Microbiology (ASM), 1998)
Rotavirus infection is the most common cause of severe infantile gastroenteritis worldwide. These viruses infect mature enterocytes of the small intestine and cause structural and functional damage, including a reduction in disaccharidase activity. It was previously hypothesized that reduced disaccharidase activity resulted from the destruction of rotavirus-infected enterocytes at the villus tips. However, this pathophysiological model cannot explain situations in which low disaccharidase activity is observed when rotavirus-infected intestine exhibits few, if any, histopathologic changes. In a previous study, we demonstrated that the simian rotavirus strain RRV replicated in and was released from human enterocyte-like Caco-2 cells without cell destruction (N. Jourdan, M. Maurice, D. Delautier, A. M. Quero, A. L. Servin, and G. Trugnan, J. Virol. 71:8268–8278, 1997). In the present study, to reinvestigate disaccharidase expression during rotavirus infection, we studied sucrase-isomaltase (SI) in RRV-infected Caco-2 cells. We showed that SI activity and apical expression were specifically and selectively decreased by RRV infection without apparent cell destruction. Using pulse-chase experiments and cell surface biotinylation, we demonstrated that RRV infection did not affect SI biosynthesis, maturation, or stability but induced the blockade of SI transport to the brush border. Using confocal laser scanning microscopy, we showed that RRV infection induces important alterations of the cytoskeleton that correlate with decreased SI apical surface expression. These results lead us to propose an alternate model to explain the pathophysiology associated with rotavirus infection.